Pengaruh Alokasi Dana Desa Terhadap Belanja Desa Dan Kemiskinan - Ratna Sari Dewi; Ova Novi Irama (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2018)
The purpose of this study was to find out and analyze the direct and indirect effects of village fund allocation on village expenditure and poverty. The population in the study of 81 village governments in North Sumatra Province began, data was taken from 2014 to 2016. Determination of the number of samples using purposive sampling method that is with the criteria that is owned by the existence of village income and expenditure budget report data and the poverty level of the village government in North Sumatra Province. The results showed that the allocation of village funds had a direct effect on poverty, but the allocation of village funds did not have an indirect effect on poverty, thus village expenditure was not an intervening variable between village fund allocation and poverty.The purpose of this study was to find out and analyze the direct and indirect effects of village fund allocation on village expenditure and poverty. The population in the study of 81 village governments in North Sumatra Province began, data was taken from 2014 to 2016.Determination of the number of samples using purposive sampling method that is with the criteria that is owned by the existence of village income and expenditure budget report data and the poverty level of the village government in North Sumatra Province. The results showed that the allocation of village funds had a direct effect on poverty, but the allocation of village funds did not have an indirect effect on poverty, thus village expenditure was not an intervening variable between village fund allocation and poverty.